The roles of actors in nature-positive transformations - Jennifer Yarnold; Josie Carwardine; Sandra Oliver; Yuwan Malakar; James D. Langston; Ilisapeci Lyons; Anthony O’Grady; Michael Dunlop; Piers Dunstan; Sam Nicol (Ambio, 2026)

Exploring the risks and benefits of flexibility in biodiversity offset location in a case study of migratory shorebirds - Nicole Shumway; Megan I. Saunders; Sam Nicol; Richard A. Fuller; Noam Ben‐Moshe; Takuya Iwamura; Sun W. Kim; Nicholas J. Murray; James E. M. Watson; Martine Maron (Conservation Biology, 2023)
Biodiversity offsets aim to counterbalance the residual impacts of development on species and ecosystems. Guidance documents explicitly recommend that biodiversity offset actions be located close to the location of impact because of higher potential for similar ecological conditions, but allowing greater spatial flexibility has been proposed. We examined the circumstances under which offsets distant from the impact location could be more likely to achieve no net loss or provide better ecological outcomes than offsets close to the impact area. We applied a graphical model for migratory shorebirds in the East Asian–Australasian Flyway as a case study to explore the problems that arise when incorporating spatial flexibility into offset planning. Spatially flexible offsets may alleviate impacts more effectively than local offsets; however, the risks involved can be substantial. For our case study, there were inadequate data to make robust conclusions about the effectiveness and equivalence of distant habitat‐based offsets for migratory shorebirds. Decisions around offset placement should be driven by the potential to achieve equivalent ecological outcomes; however, when considering more distant offsets, there is a need to evaluate the likely increased risks alongside the potential benefits. Although spatially flexible offsets have the potential to provide more cost‐effective biodiversity outcomes and more cobenefits, our case study showed the difficulty of demonstrating these benefits in practice and the potential risks that need to be considered to ensure effective offset placement.

Decision support for the Ecosystem-Based Management of a Range-Extending Species in a Global Marine Hotspot Presents Effective Strategies and Challenges - Lucy M. Robinson; Martin P. Marzloff; Ingrid van Putten; Gretta Pecl; Sarah Jennings; Sam Nicol; Alistair J. Hobday; Sean Tracey; Klaas Hartmann; Marcus Haward; Stewart Frusher (Ecosystems, 2023)

Can Stomach Content and Microbiomes of Tuna Provide Near Real-Time Detection of Ecosystem Composition in the Pacific Ocean? - Alejandro Trujillo-González; Teng Li; Joanne Potts; Simon Nicol; Valerie Allain; Sam C. Godwin; Elodie Vourey; Annie Portal; Brian Kumasi; Thomas Usu; Allen Rodrigo; Dianne Gleeson (Frontiers in Marine Science, 2022)
This preliminary study used DNA metabarcoding to test whether the stomach content and gut microbiome of tuna could be a viable near real-time monitoring tool for detecting composition and change in oceanic ecosystems. The gut content of skipjack ( Katsuwonus pelamis , n=55) and yellowfin tuna ( Thunnus albacares , n=46) captured in the Pacific Ocean during El Niño Southern Oscillation events (ENSO) between 2015-2017 were examined by high throughput sequencing and complemented by morphological assessments to identify fishes, crustaceans and cephalopods in the stomach content. Gut microbiome was examined solely by high throughput sequencing. Stomach content and gut microbiome were compared between tuna species, ENSO events and capture location using generalised linear models. The full model (tuna species, capture location and interaction with ENSO) best explained fish prey composition, while capture location and ENSO weakly explained the composition of crustaceans and cephalopods. Skipjack and yellowfin tuna captured near coastal areas (Longitude<170°W) showed a greater diversity of prey compared to fish captured in oceanic regions of the Pacific, while Thunnus albacares showed a much more diverse stomach content than K. pelamis (21 fish, eight cephalopods and six crustaceans). Fish captured during La Niña events showed higher prey diversity compared to fish captured during El Niño. Tuna species best explained differences in gut microbiome to the Phylum level, while no model explained gut microbiome differences to the Order or Family level. This preliminary study shows that capture location and ENSO events explained differences in stomach content of K. pelamis and T. albacares, while tuna species best explained gut microbiome assemblages to the Phylum level.

Retraction Note to: Structured Decision-Making Identifies Effective Strategies and Potential Barriers for Ecosystem-Based Management of a Range-Extending Species in a Global Marine Hotspot - Lucy M. Robinson; Martin P. Marzloff; Ingrid van Putten; Gretta Pecl; Sarah Jennings; Sam Nicol; Alistair J. Hobday; Sean Tracey; Klaas Hartmann; Marcus Haward; Stewart Frusher (Ecosystems, 2021)

Evaluating the Ecological Benefits of Management Actions to Complement Environmental Flows in River Systems - Sam Nicol; J. Angus Webb; Rebecca E. Lester; Marcus Cooling; Paul Brown; Ian Cresswell; Heather M. McGinness; Susan M. Cuddy; Lee J. Baumgartner; Daryl Nielsen; Martin Mallen-Cooper; Danial Stratford (Environmental Management, 2021)

Quantitative tools for implementing the new definition of significant portion of the range in the U.S. Endangered Species Act - Julia E. Earl; Sam Nicol; Ruscena Wiederholt; Jay E. Diffendorfer; Darius Semmens; D. T. Tyler Flockhart; Brady J. Mattsson; Gary McCracken; D. Ryan Norris; Wayne E. Thogmartin; Laura López‐Hoffman (Conservation Biology, 2018)
In 2014, the Fish and Wildlife Service (FWS) and National Marine Fisheries Service announced a new policy interpretation for the U.S. Endangered Species Act (ESA). According to the act, a species must be listed as threatened or endangered if it is determined to be threatened or endangered in a significant portion of its range (SPR). The 2014 policy seeks to provide consistency by establishing that a portion of the range should be considered significant if the associated individuals’ “removal would cause the entire species to become endangered or threatened.” We reviewed 20 quantitative techniques used to assess whether a portion of a species’ range is significant according to the new guidance. Our assessments are based on the 3R criteria—redundancy (i.e., buffering from catastrophe), resiliency (i.e., ability to withstand stochasticity), and representation (i.e., ability to evolve)—that the FWS uses to determine if a species merits listing. We identified data needs for each quantitative technique and considered which methods could be implemented given the data limitations typical of rare species. We also identified proxies for the 3Rs that may be used with limited data. To assess potential data availability, we evaluated 7 example species by accessing data in their species status assessments, which document all the information used during a listing decision. In all species, an SPR could be evaluated with at least one metric for each of the 3Rs robustly or with substantial assumptions. Resiliency assessments appeared most constrained by limited data, and many species lacked information on connectivity between subpopulations, genetic variation, and spatial variability in vital rates. These data gaps will likely make SPR assessments for species with complex life histories or that cross national boundaries difficult. Although we reviewed techniques for the ESA, other countries require identification of significant areas and could benefit from this research.

Setting conservation priorities for migratory networks under uncertainty - Kiran L. Dhanjal‐Adams; Marcel Klaassen; Sam Nicol; Hugh P. Possingham; Iadine Chadès; Richard A. Fuller (Conservation Biology, 2017)
Conserving migratory species requires protecting connected habitat along the pathways they travel. Despite recent improvements in tracking animal movements, migratory connectivity remains poorly resolved at a population level for the vast majority of species, thus conservation prioritization is hampered. To address this data limitation, we developed a novel approach to spatial prioritization based on a model of potential connectivity derived from empirical data on species abundance and distance traveled between sites during migration. We applied the approach to migratory shorebirds of the East Asian‐Australasian Flyway. Conservation strategies that prioritized sites based on connectivity and abundance metrics together maintained larger populations of birds than strategies that prioritized sites based only on abundance metrics. The conservation value of a site therefore depended on both its capacity to support migratory animals and its position within the migratory pathway; the loss of crucial sites led to partial or total population collapse. We suggest that conservation approaches that prioritize sites supporting large populations of migrants should, where possible, also include data on the spatial arrangement of sites.

Optimization methods to solve adaptive management problems - Iadine Chadès; Sam Nicol; Tracy M. Rout; Martin Péron; Yann Dujardin; Jean-Baptiste Pichancourt; Alan Hastings; Cindy E. Hauser (Theoretical Ecology, 2017)

Priority threat management of invasive animals to protect biodiversity under climate change - Jennifer Firn; Ramona Maggini; Iadine Chadès; Sam Nicol; Belinda Walters; Andy Reeson; Tara G. Martin; Hugh P. Possingham; Jean‐Baptiste Pichancourt; Rocio Ponce‐Reyes; Josie Carwardine (Global Change Biology, 2015)
Climate change is a major threat to global biodiversity, and its impacts can act synergistically to heighten the severity of other threats. Most research on projecting species range shifts under climate change has not been translated to informing priority management strategies on the ground. We develop a prioritization framework to assess strategies for managing threats to biodiversity under climate change and apply it to the management of invasive animal species across one‐sixth of the Australian continent, the Lake Eyre Basin. We collected information from key stakeholders and experts on the impacts of invasive animals on 148 of the region's most threatened species and 11 potential strategies. Assisted by models of current distributions of threatened species and their projected distributions, experts estimated the cost, feasibility, and potential benefits of each strategy for improving the persistence of threatened species with and without climate change. We discover that the relative cost‐effectiveness of invasive animal control strategies is robust to climate change, with the management of feral pigs being the highest priority for conserving threatened species overall. Complementary sets of strategies to protect as many threatened species as possible under limited budgets change when climate change is considered, with additional strategies required to avoid impending extinctions from the region. Overall, we find that the ranking of strategies by cost‐effectiveness was relatively unaffected by including climate change into decision‐making, even though the benefits of the strategies were lower. Future climate conditions and impacts on range shifts become most important to consider when designing comprehensive management plans for the control of invasive animals under limited budgets to maximize the number of threatened species that can be protected.

Benefits of integrating complementarity into priority threat management - Iadine Chadés; Sam Nicol; Stephen van Leeuwen; Belinda Walters; Jennifer Firn; Andrew Reeson; Tara G. Martin; Josie Carwardine (Conservation Biology, 2015)
Conservation decision tools based on cost‐effectiveness analysis are used to assess threat management strategies for improving species persistence. These approaches rank alternative strategies by their benefit to cost ratio but may fail to identify the optimal sets of strategies to implement under limited budgets because they do not account for redundancies. We devised a multiobjective optimization approach in which the complementarity principle is applied to identify the sets of threat management strategies that protect the most species for any budget. We used our approach to prioritize threat management strategies for 53 species of conservation concern in the Pilbara, Australia. We followed a structured elicitation approach to collect information on the benefits and costs of implementing 17 different conservation strategies during a 3‐day workshop with 49 stakeholders and experts in the biodiversity, conservation, and management of the Pilbara. We compared the performance of our complementarity priority threat management approach with a current cost‐effectiveness ranking approach. A complementary set of 3 strategies: domestic herbivore management, fire management and research, and sanctuaries provided all species with >50% chance of persistence for $4.7 million/year over 20 years. Achieving the same result cost almost twice as much ($9.71 million/year) when strategies were selected by their cost‐effectiveness ranks alone. Our results show that complementarity of management benefits has the potential to double the impact of priority threat management approaches.

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate - MORENA MILLS; SAM NICOL; JESSIE A. WELLS; JOSÉ J. LAHOZ‐MONFORT; BRENDAN WINTLE; MICHAEL BODE; MARTIN WARDROP; TERRY WALSHE; WILLIAM J. M. PROBERT; MICHAEL C. RUNGE; HUGH P. POSSINGHAM; EVE MCDONALD MADDEN (Conservation Biology, 2014)
Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate‐change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that integrates these costs and benefits with probabilistic forecasts for the extent of sea‐level rise to find a balance between coastal ecosystem protection and moderate coastal development. Here, we suggest that instead of keeping their options open managers should incorporate uncertain sea‐level rise predictions into a decision‐making framework that evaluates the benefits and costs of conservation and development. In our example, based on plausible scenarios for sea‐level rise and assuming a risk‐neutral decision maker, we found that substantial development could be accommodated with negligible loss of environmental assets. Characterization of the Pareto efficiency of conservation and development outcomes provides valuable insight into the intensity of trade‐offs between development and conservation. However, additional work is required to improve understanding of the consequences of alternative spatial plans and the value judgments and risk preferences of decision makers and stakeholders. Minimizando el Costo de Mantener Opciones Abiertas para la Conservación en un Clima Cambiante

Optimal water depth management on river-fed National Wildlife Refuges in a changing climate - Sam Nicol; Brad Griffith; Jane Austin; Christine M. Hunter (Climatic Change, 2014)